Metabolic Signature and Obstructive Sleep Apnea in Nepalese Patients - Verma, Avatar; Bhatta, Narendra; Mishra, Deebya Raj; Shahi, Rejina; Uprety, Augraj; Aryal, Prakash; Yadav, Devesh Kumar; Lama, Urmila (Nepalese Respiratory Journal, 2023)
Introduction: Untreated Obstructive Sleep Apnea (OSA) causes sleep related symptoms and also causes increased incidence of RTA, cardiovascular diseases and all cause mortality. Currently OSA has been recognized as the consequence of number of interrelated metabolic and oxidative pathologies. As there are limited data of association of OSA with metabolic stress and its correlation with severity of OSA, study of metabolic profile of these patients in view of defining the Metabolic signature of OSA was carried out in eastern Nepal. Objectives: To study metabolic profile of OSA and its association with clinical severity. Methods: Hospital based descriptive cross sectional study. Biochemical profile results related to metabolic –oxidative pathway of the OSA patients were obtained. Quantitative and qualitative data were obtained. Quantitative data were compared using Mann–Whitney test while qualitative variables compared using Pearson χ2. Correlation was carried out using Pearson and Spearman’s test. P-value<0.05 considered significant. Results: 33 patients of OSA were enrolled. Majority of patients had deranged metabolic and oxidative parameters despite mild OSA. Among metabolic stress parameters, most commonly deranged were decreased high density lipoprotein (HDL), increased mean arterial pressure (MAP), waist circumference (WC) and raised fasting blood sugar (FBS). Increased MAP and increased WC was significantly corelated with severity. Conclusion: Besides symptom complex, OSA is also harbinger of metabolic stress that can lead to various cardiometabolic diseases and premature mortality thus early recognition and treatment can mitigate these consequences.